Approximation of functions from generalized Nikol’skii– Besov classes by entire functions in Lebesgue spaces(in Ukrainian) - V. V. Myroniuk; S. Ya. Yanchenko (Математичні Студії, 2013)
Exact-order estimates for the approximations of functions ofclasses $S^{Omega}_{p,{heta}}B(mathbbR^d)$ by entirefunctions with the spectrum of a special form in the space$L_q(mathbbR^d)$ for some relations between the parameters$p$ and $q$, are established.